Drug resistance in Campylobacter jejuni, C coli, and C lari isolated from humans in north west England and Wales, 1997. Issue 11 (1st November 1999) - Thwaites, R T; Frost, J A
Abstract : AIMS: To test the sensitivity of strains of Campylobacter species isolated from humans in England and Wales against a range of antimicrobial agents for the purpose of monitoring therapeutic efficacy and as an epidemiological marker. METHODS: An agar dilution breakpoint technique was used to screen isolates against ampicillin, chloramphenicol, gentamicin, kanamycin, neomycin, tetracycline, nalidixic acid, ciprofloxacin, and erythromycin. Minimal inhibitory concentrations (MIC) were also determined for a sample of quinolone resistant strains. RESULTS: Approximately 50% of strains tested were resistant to at least one drug. Strains which were resistant to four or more of the drugs tested were classified as multiresistant; this occurred in 11.3% of C jejuni, 19.9% of C coli, and 63.6% of C lari. Resistance to erythromycin occurred in 1.0% of C jejuni and 12.8% of C coli. Resistance to quinolones occurred in 12% of strains, with a ciprofloxacin MIC of > 8 mg/l and a nalidixic acid MIC of > 256 mg/l; a further 4% of strains had intermediate resistance with a ciprofloxacin MIC of between 0.5 and 2 mg/l (fully sensitive strains, 0.25 mg/l or less) and a nalidixic acid MIC of between 32 and 64 mg/l (fully sensitive strains, 8 mg/l or less). CONCLUSIONS: Resistance to quinolones in campylobacters from human infection may relate to clinical overuse or use of fluoroquinolones in animal husbandry. Both veterinary and clinical use should be reconsidered and fluoroquinolone drugs used only as a treatment for serious infections requiring hospital admission. Erythromycin resistance is still rare in C jejuni but much more common in C coli.